First complete genome sequence of canine bocavirus 2 in mainland China. (July 2017) - Zhai, S.-L.; Lin, T.; Chen, Y.-W.; Liu, R.; Lv, D.-H.; Wen, X.-H.; Zhu, X.-L.; Wang, D.; Li, F.; Wei, W.-K.
Abstract: We obtained the first full-length genome sequence of canine bocavirus 2 (CBoV2) from the faeces of a healthy dog in Guangzhou city, Guangdong province, mainland China. The genome of GZHD15 consisted of 5059 nucleotides. Sequence analysis suggested that GZHD15 was close to a previously circulated Hong Kong isolate.